TRANSFORMASI KOMPETENSI GURU MADRASAH TSANAWIYAH (MTs) MELALUI DESAIN PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI - Isniar Budiarti,; Dicky Rizkyka Ramadan Siregar, (Jurnal Cakrawala Ilmiah, 2025)
This community service program aimed to transform the competencies of teachers at Madrasah Tsanawiyah (MTs) Cahaya Harapan in designing interactive, technology-based learning. Initial observations revealed that most teachers still relied on conventional teaching methods and encountered difficulties in utilizing digital presentation tools creatively. To address this challenge, a hands-on training session was conducted using Microsoft PowerPoint as an engaging and interactive instructional medium. The training methods included lectures, demonstrations, independent practice, and pre-test and post-test evaluations. The results showed a significant improvement in teachers' abilities to design visually appealing and interactive learning media. Furthermore, the program fostered the formation of a teacher learning community and promoted a collaborative spirit in developing instructional innovations. This initiative is expected to serve as a model for transforming teacher competencies to meet the demands of 21st-century education.